Potret Struktur Patriarki melalui Bahasa Seksis pada Player Perempuan dalam Game Mobile Legends Bang Bang - Morty, Sa'adiah Dwitiya; Damaiyanti, Varinia Pura (Huma: Jurnal Sosiologi, 2024)
The entry of women into online games that are dominated by men creates a new case where women become victims of discrimination using sexist language. This research was conducted in the Miaw Ladies community group, which is a community specifically for women in the mobile game Legends Bang Bang. This research aims to find out and provide an overview of the sexist language that is often encountered by female players in the mobile game Legends Bang Bang and wants to know how patriarchal structures are maintained through sexist language in the game. This research uses qualitative research with a Feminist Method approach. The results of the research found that there were two types of sexist language experienced by female players, namely sexist language which leads to obscenity and derogatory sexist language. Obscene sexist language found in the mobile game Legends Bang Bang equates women with sex workers, equates women with vaginas, and even insults players' parents by calling them sluts. Sexist language demeans the majority of female players as being stupid in the field of online gaming, deeming women inappropriate to play online games, and belittling women's abilities in the field of online gaming. The results found are in accordance with Luce Irigaray's opinion that language is a tool used to maintain patriarchy in society by insulting and belittling women and feeling superior in the field of gaming. Mobile Legends: Bang Bang game players should be more respectful and appreciative of fellow players without discriminating against any gender.